Expansion of an osteopontin‐expressing T follicular helper cell subset correlates with autoimmunity in B6.Sle1b mice and is suppressed by the H1‐isoform of the Slamf6 receptor. Issue 8 (29th April 2013) - Keszei, Marton; Detre, Cynthia; Castro, Wilson; Magelky, Erica; O'Keeffe, Michael; Kis‐Toth, Katalin; Tsokos, George C.; Wang, Ninghai; Terhorst, Cox
Abstract : The costimulatory receptor Slamf6 partially controls lupus‐related autoimmunity in congenic Sle1b mice; for instance, the presence of the protein isoform Slamf6‐H1 in Sle1b.Slamf6‐H1 mice mitigates disease. Here, we report that young Sle1b mice, but not Sle1b.Slamf6‐H1 or B6 mice, contain a memory T‐helper cell subset identified by ∗∗∗ [mt]2‐fold increase in expression of 17 genes, chief among which is Spp1, encoding the cytokine osteopontin (OPN). These T follicular helper (TFH ) cells, including OPN + T FH cells, expand concomitantly with severity of the disease. By contrast, Sle1b.Slamf6‐H1 or Sle1b.SAP – / – mice do not develop autoantibodies and the number of TFH cells is 5 times lower than in age‐matched Sle1b mice. By comparing Sle1b and Sle1b.OPN – / – mice, we find that the lack of OPN expression impedes early autoantibody production. Furthermore, on the adoptive transfer of Sle1b.OPN – / – CD4 + T cells into bm12 recipients autoantibody production and germinal center formation is reduced compared to recipients of Sle1b.OPN+/+ CD4 + T cells. We propose a model in which OPN provides a survival signal for a precursor TFH cell subset, which is a key factor in autoimmunity. Keszei, M., Detre, C., Castro, W., Magelky, E., O'Keeffe, M., Kis‐Toth, K., Tsokos, G. C., Wang, N., Terhorst, C. Expansion of an osteopontin‐expressing T follicular helper cell subset correlates with autoimmunity in B6.Sle1b mice and is suppressed by the H1‐isoform of the Slamf6 receptor. FASEB J. 27, 3123–3131 (2013). www.fasebj.org